Evaluation of competency and job satisfaction by positive human psychology among physical education teachers at the university level: A systematic review - Yan, Tingting; Teo, Eng Wah; Lim, Boon Hooi; Lin, Bo (Frontiers in Psychology, 2022)
The study aimed to determine how a teacher’s competency at the university level related to professional commitment and job satisfaction. This systematic review intends to determine physical education teachers’ competency and job satisfaction. One of the main objectives of physical education programs is to increase various activities of the student, especially physical activities and participation in it. Students who participate in physical activities feel a variety of emotions, and these may enhance their mental and physical well-being. The study concerns the teachers’ satisfaction in effectively influencing and teaching the students. Job satisfaction refers to teachers’ feelings and positive attitudes toward their work. The five components of job satisfaction are pay, promotion, supervision, co-workers, and work itself. Job satisfaction is broken down into these five components. Work as a teacher is one of the most important components of a teacher’s or teacher’s success at work and one of the key criteria for the school’s achievement. Electronic libraries were explored, including Google Scholar, PubMed, Embase, Bing Academic, and Cochrane. Appropriate keywords were used for searching the literature. By applying certain inclusion and exclusion criteria, the final studies were selected for evaluation. The study’s findings showed that physical education instructors had high levels of teaching competence and moderate levels of job satisfaction. The findings demonstrated that job satisfaction and competency rise when degree levels rise, and relatedness, skill, and autonomy self-motivation ensue. Students’ motivation for physical education was greatly influenced by the teachers’ support, motivation, and mastery climate. The self-determination theory positively enhances physical education from the teacher’s perspective on PE, increasing instruction effectiveness.